AUGMENTED REALITY DEVELOPMENT AS SUPPORTING MEDIA OF POLITEKNIK KEDIRI PROMOTION - Kusuma, Selvia Ferdiana (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2018)
In this digital era, the presentation of information as a media campaign in the form of brochures and pamphlets is increasingly left out. Besides being considered boring it also looks less interactive. The advent of AR technology that can combine real and virtual images in 3-dimensional form projected onto a screen or monitor can be used as a solution in delivering more interactive information. But Politeknik Kediri has not implemented it. The brochure of Politeknik Kediri as one of the media campaign has not been integrated with augmented reality technology, so it seems less interesting. Therefore, we create an android-based application that can display the visualization of Politeknik Kediri using augmented reality to support promotion. Through this research, it is expected that the media campaign of Politeknik Kediri can be more interesting, so that many prospective students who are interested to join Politeknik Kediri especially Informatics Engineering Department. This research is done through 6 stages: analyze the needs, perform system design, hierarchy, application implementation, and application testing. While the software used in this study is Vuforia SDK, An-droid SDK, Unity3D, and Blender.